2000
DOI: 10.1590/s0100-879x2000000900005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma pneumoniae and Chlamydia pneumoniae in ruptured atherosclerotic plaques

Abstract: This paper reports what is apparently the first observation of Mycoplasma pneumoniae in association with Chlamydia pneumoniae in thrombosed ruptured atheromas. We performed electron microscopy and in situ hybridization in specimens from three patients who died of acute myocardial infarction. These patients had typical symptoms of acute ischemic syndrome. Mycoplasmas were present mainly in the lipid core of the ruptured thrombosed plaque. Vulnerable atheromas are rich in cholesterol and may favor the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
14

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 13 publications
2
36
0
14
Order By: Relevance
“…In a sequence of the reported studies 22 , we observed that, in addition to C. pneumoniae, another bacterium is found in unstable atherosclerotic plaques: Mycoplasma pneumoniae (M. pneumoniae).…”
mentioning
confidence: 89%
“…In a sequence of the reported studies 22 , we observed that, in addition to C. pneumoniae, another bacterium is found in unstable atherosclerotic plaques: Mycoplasma pneumoniae (M. pneumoniae).…”
mentioning
confidence: 89%
“…We have previously reported that Chlamydia pneumoniae and Mycoplasma pneumoniae are present in atherosclerotic plaques 15,17,18 . Given the similarity between atherosclerosis and aortic valve stenosis, we hypothesized that such agents may also be present in AS and play an important role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Chlamydia pneumoniae (CP) has been suggested to be involved in the pathogenesis of atherosclerosis, related with gene polymorphisms 14 and inflammation 15 but this still is a controversial matter [16][17][18] . CP has also been associated with the inflammatory processes of aortic valve lesions 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Higuchi et ai 2000), com repercussões patológicas. Da adesão dessas plaquetas e sua agregação pode-se formar no local um trombo, causando a oclusão parcial ou total da luz do vaso e conduzindo a sintomas da doença coronariana, como isquemia e infarto do miocárdio (Libby, 1998).…”
Section: 1ntroduçãounclassified